Effect of W-Mo balance and boron nitrides on creep rupture ductility of 9Cr steel. (4th July 2019) - Abe, Fujio; Ohba, Toshio; Miyazaki, Hideko; Toda, Yoshiaki; Tabuchi, Masaaki
ABSTRACT: The effect of W-Mo balance and boron nitrides (BN) on creep rupture ductility has been investigated for five heats of 9% Cr steel with 1.5% Mo equivalent, 0.003% boron and 0.05% nitrogen at 600 o C, 650 o C and 700 o C. The maximum time to rupture was 68, 718 h at 650 o C. The reduction of area (RA) slightly decreases for up to about 8000 and 1000 h at 600 and 650 o C, respectively, while it significantly decreases above those. The BN particles are responsible for the degradation in RA at low stresses and long times by accelerating the formation of creep voids. At high stresses and short times, the RA decreases with increasing time to rupture and with increasing W concentration and concomitantly with decreasing Mo concentration. The rupture ductility is evaluated by using a semi-logarithmic diagram of the RA and total elongation, showing the necking dominant and void swelling dominant regions.